2015
DOI: 10.5114/wo.2014.47135
|View full text |Cite
|
Sign up to set email alerts
|

Review Epigenetic mechanisms of induced pluripotency

Abstract: Reprogramming of somatic cells to induced pluripotent stem cells (iPSCs) requires profound alterations in the epigenetic landscape. During reprogramming, a change in chromatin structure resets the gene expression and stabilises self-renewal. Reprogramming is a highly inefficient process, in part due to multiple epigenetic barriers. Although many epigenetic factors have already been shown to affect self-renewal and pluripotency in embryonic stem cells (ESCs), only a few of them have been examined in the context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 111 publications
0
19
0
1
Order By: Relevance
“…Several studies have shown that the epigenetic landscape of a cell is drastically remodeled during reprogramming enabling the transcription of pluripotency-associated and the repression of differentiation-promoting genes [reviewed in (59)]. There are a number of studies which display a connection between miRNAs and epigenetic modifiers further proving the versatility of miRNAs.…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 98%
“…Several studies have shown that the epigenetic landscape of a cell is drastically remodeled during reprogramming enabling the transcription of pluripotency-associated and the repression of differentiation-promoting genes [reviewed in (59)]. There are a number of studies which display a connection between miRNAs and epigenetic modifiers further proving the versatility of miRNAs.…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 98%
“…The methylation is established by de novo methyltransferases Dnmt3a and Dmnt3b and preserved by the maintenance methyltransferase Dnmt1 ( Smith & Meissner, 2013 ). During reprogramming, the methylation marks are removed from these endogenous pluripotency genes to allow for their transcription, and tissue-specific genes are hypermethylated ( Gladych et al, 2015 ; Berdasco & Estellar, 2011 ). Indeed, manipulation of the DNA and chromatin modifications by certain small molecules can significantly improve iPSC formation ( Huangfu et al, 2008a , 2008b ; Li et al, 2009b ; Feldman et al, 2006 ) (see reprogramming factors–epigenetic modifiers).…”
Section: Molecular Mechanism Of Induced Pluripotencymentioning
confidence: 99%
“…The bivalent domains are almost exclusively found in pluripotent stem cells, and their restoration represents a vital step in the reprogramming process. During reprogramming, repressive H3K9me3 marks present on the endogenous pluripotency genes (Oct4, Sox2, and Nanog) are gradually replaced by the transcriptionally active H3K4me3 ( Gladych et al, 2015 ). The loss of the H3K9me3 marks allows access of OSKM transgenes to their target regions thus activating the autoregulatory loop.…”
Section: Molecular Mechanism Of Induced Pluripotencymentioning
confidence: 99%
“…Somatic cell reprogramming to induced pluripotent stem cells is also dependent on massive alterations within the epigenomic profile of the cells [7,8]. Successful reprogramming reversely mirrors early developmental processes and requires the elimination of epigenetic barriers [9,10] to acquire open chromatin state that is characteristic to stem cells [8,11]. The maintenance of the epigenome becomes more error-prone with age, thus leading to so-called "epigenetic drift"-accumulation of epigenomic aberrations.…”
Section: Introductionmentioning
confidence: 99%